Little Ghost Makes a Friend - Willis, Maggie Edkins (New York : Simon & Schuster Books for Young Readers, 2024)
A shy ghost learns the secret to making a friend is being his spooky, sparkly self.
Keywords: Ghost stories; Bashfulness in children -- Juvenile fiction; Friendship in children -- Juvenile fiction; Self-perception in children -- Juvenile fiction; Identity (Psychology) -- Juvenile fiction; Halloween -- Juvenile fiction; Ghosts -- Fiction; Bashfulness -- Fiction; Friendship -- Fiction; Self-perception -- Fiction; Identity -- Fiction; Halloween -- Fiction; Picture books; Picture books